(untitled) (Bangladesh Journal of Botany, 2025)
This study examined the effects of fresh crude extract from 215 plants on the mortality rate of third-instar larvae of Aedes aegypti after a 24-hour exposure. Twenty five plants demonstrated a high mortality rate (up to 80%) at five different concentrations. The LC50, LC90, and LC95 values of the tested plants showed that 15 plants were with 100% larvicidal potential. Stemona tuberosa showed the highest efficacy against Aedes larvae having LC50 = 3.78, LC90 = 7.51, and LC95 = 7.97, while Jatropha gossypifolia showed the lowest efficacy i.e., LC50 = 6.58, LC90 =11.23, and LC95 = 11.31. The extracts from Acmella radicans, Allium sativum, and Oxalis violacea exhibited a similar LC50 value of 3.99, indicating their high potency. Hence, the tested plants are a potential source of bioactive compounds that may work as a potential alternative to chemical mosquito larvicides. Bangladesh J. Bot. 54(1): 54-60, 2025 (March)